Tensile test simulation of high-carbon steel by discrete element method. Issue 4 (13th June 2016) - Chen, Guangming; Schott, Dingena L.; Lodewijks, Gabriel
Abstract : Purpose: – The tensile test is one of the fundamental experiments used to evaluate material properties. Simulating a tensile test can be a replacement of experiments to determine mechanical parameters of a continuous material. The paper aims to discuss these issues. Design/methodology/approach: – This research uses a new approach to model a tensile test of a high-carbon steel on the basis of discrete element method (DEM). In this research, the tensile test specimen was created by using a DEM packing theory. The particle-particle bond model was used to establish the internal forces of the tensile test specimen. The particle-particle bond model was first tested by performing two-particle tensile test, then was adopted to simulate tensile tests of the high-carbon steel by using 3, 678 particles. Findings: – This research has successfully revealed the relationships between the DEM parameters and mechanical parameters by modelling a tensile test. The parametric study demonstrates that the particle physical radius, particle contact radius and bond disc radius can significantly influence ultimate stress and Young's modulus of the specimen, whereas they slightly impact elongation at fracture. Increasing the normal and shear stiffness, the critical normal and shear stiffness can enable the increase of ultimate stress, however, up to maximum values. Research limitations/implications: – To improve the particle-particle bond model to simulate a tensile test for high-carbon steel, the damping factors for compensating energy loss from transition of particle motions and failure of bonds are required. Practical implications: – This work reinforces the knowledge of applying DEM to model continuous materials. Originality/value: – This research illustrates a new approach to model a tensile test of a high-carbon steel on the basis of DEM.